Conflict Principle lex voluntaris in Civil Legislation Republic of Armenia - Haykyants, Armen (Bulletin of Yerevan University C: Jurisprudence, 2024)
Article 3 of the Civil Code of the Republic of Armenia enshrines the principle of autonomy of the will. In the national legal science and also in practice, there are still debatable and often incomplete ideas about the essence and scope of application of the mentioned principle, challenging the extent to which the principle of the autonomy of the will is compatible with the other principle established by Article 3 of the Civil Code of the Republic of Armenia, the freedom of contract,  as well as the sufficiency of the Article 1284 of the Civil Code of the Republic of Armenia, as a tool for the realization of the principle of autonomy of the will, to provide with measures for the full application of the principle .             In the legal science the principle of autonomy of will was initially formed as a principle aimed at serving the contractual circulation, however in different legal systems, including the Republic of Armenia, the principle of autonomy of will is also applied to extra-contractual relations, and it is not yet fully discussed whether when applied to contractual and extra-contractual relations the principle of the autonomy of the will relies on the same set of tools, or whether, depending on the essence of the target relationship, the set of tools should be different. One can endlessly seek for the answers in legal practice, however, as proven by expertise, the legal practice itself turns to the arsenal of legal science to get the solutions for such cases. There is no doubt that science is the flag bearer in the science-practice cooperation, and it is science that shall provide practice with the keys to solving problems.
Keywords: principle; freedom of contract; autonomy of will; foreign law; conflict norm; content of contract; form of contract; contractual relationship; non-contractual relationship